2019
DOI: 10.3390/antibiotics8040256
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Herbal Therapy on Clinical Symptoms of Acute Lower Uncomplicated Urinary Tract Infections in Women: Secondary Analysis from a Randomized Controlled Trial

Abstract: Background: Antibiotics are commonly used as first-line treatment for acute lower uncomplicated urinary tract infections (uUTIs). However, antimicrobial resistance is a growing global problem and efficacious nonantibiotic treatment options are urgently needed. Methods: A secondary analysis was conducted with data from a randomized, controlled, double-blind trial comparing a fixed combination of extracts of restharrow root, Java tea, and goldenrod herb (Aqualibra®) to placebo in 200 women with acute lower uUTI.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 19 publications
(31 reference statements)
0
5
0
1
Order By: Relevance
“…A few investigations also evaluated its neuroprotection in epilepsy, depression, and Alzheimer’s disease(Chung et al, 2020). However, most of these studies were at the pre-clinical phase; only three clinical trials of an herbal combination containing O. aristatus proved effective in treating hypertension, metabolic syndrome(Cicero et al, 2012), and urinary tract infections(Mainini et al, 2020; Vahlensieck et al, 2019). Based on the I-T-D network and DO analysis in our study, it seems to give an insight that O. aristatus was a versatile therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A few investigations also evaluated its neuroprotection in epilepsy, depression, and Alzheimer’s disease(Chung et al, 2020). However, most of these studies were at the pre-clinical phase; only three clinical trials of an herbal combination containing O. aristatus proved effective in treating hypertension, metabolic syndrome(Cicero et al, 2012), and urinary tract infections(Mainini et al, 2020; Vahlensieck et al, 2019). Based on the I-T-D network and DO analysis in our study, it seems to give an insight that O. aristatus was a versatile therapeutic agent.…”
Section: Discussionmentioning
confidence: 99%
“…As shown in Supplementary table S2, the average molecular weight of these ingredients was about 230.59, the median was 185.22, the maximum was 492.56, and the minimum was 100. 16. The prediction results of drug characteristics shown that of the 62 active ingredients, 77.42% had good water solubility, 96.77% had good intestinal absorption, and 74.19% can permeate the blood-brain barrier (BBB).…”
Section: The Adme Parameters and Physicochemical Properties Of These Ingredientsmentioning
confidence: 99%
See 1 more Smart Citation
“…For many common and recurring infections, such as urogenital infections [ 78 , 79 ] or infections of the upper and lower respiratory tract [ 80 , 81 ], effective and safe herbal treatment options are available. For instance, herbal treatment options for uncomplicated UTI include Centaurii herba , Levistici radix , and Rosmarini folium (Canephron ® , Bio-norica SE, Neumarkt in der Oberpfalz, Germany) [ 82 ], Tropaeoli herba and Armoraciae radix (Angocin ® , Repha GmbH, Langenhagen, Germany) [ 83 , 84 ], Ononidis radix, Orthosiphonis folium, and Solidaginis herba (Aqualibra ® , MEDICE Arzneimittel Pütter GmbH & Co. KG, Iserlohn, Germany) [ 85 ], Arctostaphylos uva-ursi (e.g., Cystinol ® , Schaper & Brümmer GmbH & Co. KG, Salzgitter, Germany) [ 86 ], and cranberry [ 87 ]. Likewise, for rhinosinusitis, various herbal medicinal products exist, such as Sambuci flos , Gentianae radix , Primulae flos , Rumicis herba , and Verbenae herba (Sinupret ® , Bionorica SE, Germany) [ 88 , 89 ], cineole (e.g., Soledum ® , Cassella-med GmbH & Co. KG, Köln, Germany) [ 90 ], myrtol (Gelomyrtol ® , G. Pohl-Boskamp GmbH & Co. KG, Hohenlockstedt, Germany) [ 91 ], and Pelargonium sidoides (Umckaloabo ® , Dr. Willmar Schwabe GmbH & Co. KG, Karlsruhe, Germany) [ 92 , 93 , 94 ].…”
Section: Herbal Drugs: a Safe Treatment Alternative For Uncomplicated...mentioning
confidence: 99%
“…For many common and recurring infections, such as urogenital infections [78,79] or infections of the upper and lower respiratory tract [80,81], effective and safe herbal treatment options are available. For instance, herbal treatment options for uncomplicated UTI include Centaurii herba, Levistici radix, and Rosmarini folium (Canephron ® ) [82], Tropaeoli herba and Armoraciae radix (Angocin ® ) [83,84], Ononidis radix, Orthosiphonis folium, and Solidaginis herba (Aqualibra ® ) [85], Arctostaphylos uva ursi (e.g., Cystinol ® ) [86], and cranberry [87]. Likewise, for rhinosinusitis various herbal medicinal products exist such as Sambuci flos, Gentianae radix, Primulae flos, Rumicis herba, and Verbenae herba (Sinupret ® ) [88,89], cineole (e.g., Soledum ® ) [90], myrtol (Gelomyrtol ® ) [91] and Pelargonium sidoides (Umckaloabo ® ) [92][93][94].…”
Section: Introductionmentioning
confidence: 99%